2020
DOI: 10.5489/cuaj.6637
|View full text |Cite
|
Sign up to set email alerts
|

Point-of-care ultrasound in urology: Design and evaluation of a feasible introductory training program for Canadian residents

Abstract: Introduction: Point-of-care ultrasound (POCUS) is an increasingly used bedside tool. Applications in urology include the assessment of an undifferentiated acute scrotum, renal colic, and the guidance of suprapubic catheter placement. However, the user-dependent nature of this modality necessitates appropriate use and competence. The objective of this study was to develop and evaluate a low-cost, feasible, and guideline-based introductory POCUS program for Canadian urology residents. Methods: Residents fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…In addition, all residents demonstrated an interest in pocus and stated that pocus training should be integrated into Canadian urology residency programs. 13 Considering the positive outcomes of this study, urologists can refer to this training model to create their own educational programs for residents. Fortunately, the study used homemade imaging simulators instead of simulated patients, which renders it cost-effective and reproducible at any academic urology center.…”
Section: Cuaj -Original Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, all residents demonstrated an interest in pocus and stated that pocus training should be integrated into Canadian urology residency programs. 13 Considering the positive outcomes of this study, urologists can refer to this training model to create their own educational programs for residents. Fortunately, the study used homemade imaging simulators instead of simulated patients, which renders it cost-effective and reproducible at any academic urology center.…”
Section: Cuaj -Original Researchmentioning
confidence: 99%
“…It has a variety of applications in urology, including the timely diagnosis of an undifferentiated acute scrotum, the assessment of hydronephrosis in renal colic, and guidance for suprapubic catheter placement; however, operator competence is critical as it is a user-dependent modality. 13 Lack of training can lead to misdiagnosis, poor clinical management, and adverse patient outcomes. 14,15 Our study demonstrated that most residents did not think they would have the knowledge to perform their own pocus by the end of their residency.…”
Section: Cuaj -Original Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…14 We also plan to evaluate the model during our urology residency program's annual point of care US (POCUS) course, which currently does not have a SPC evaluation component. 30 This course is conducted during an academic half-day and all urology residents in our program attend, which allows for evaluation of residents at different levels of training. To explore options, during the most recent course, we used a thin pork chop with a bone (to simulate the pubic symphysis) to simulate the skin layer and subcutaneous tissue on the SPC model, which worked very well for US training, 30 indicating a potential improvement to the model.…”
Section: Randhawa Et Al Suprapubic Catheter Insertion Training Simulatormentioning
confidence: 99%
“…30 This course is conducted during an academic half-day and all urology residents in our program attend, which allows for evaluation of residents at different levels of training. To explore options, during the most recent course, we used a thin pork chop with a bone (to simulate the pubic symphysis) to simulate the skin layer and subcutaneous tissue on the SPC model, which worked very well for US training, 30 indicating a potential improvement to the model. This variation will need to be tested before any training for evaluation purposes occurs.…”
Section: Randhawa Et Al Suprapubic Catheter Insertion Training Simulatormentioning
confidence: 99%